Pesan Dakwah Pada Film Ajari Aku Islam Karya Jaymes Riyanto - Rizqiyanabila Rizqiyanabila; Fahruddin Eko Hardiyanto (BLAZE : Jurnal Bahasa dan Sastra dalam Pendidikan Linguistik dan Pengembangan, 2024)
Da'wah in the world of film is increasingly developing, as reflected in the film Ajari Aku Islam, which depicts the dynamics of the relationship between a non-Muslim man and a Muslim woman when they fall in love. This film highlights the struggle of a non-Muslim young man who is persistent in studying the Islamic religion, starting from love for individuals and then developing into love for religion. This theme is relevant to the phenomenon of interfaith love which often faces obstacles, such as disapproval from the family. In fact, some prefer to embrace their partner's religion, distancing themselves from their previous beliefs. Therefore, it is important to examine the preaching messages embedded in this film, using Charles Sanders Peirce's semiotic approach. This research aims to reveal the message of da'wah through analysis of icons, indices and symbols contained in films. The type of research used is descriptive qualitative. The research results show that in its 93 minute duration, the film conveys da'wah messages about faith, sharia, morals and muamalah. The preaching message is an illustration of the dynamics of love across religions, and this film can be a guide for those who face similar situations.